Impact of Fleet Management on an Organization's Performance. - Richard Paul Mujuzi (Uganda Christian University, 2023)
Fleet management is the use of a set of vehicles in order to provide a service to a third-party, or to perform an activity internally in an organization, in the most efficient and productive manner with a determined level of service and cost. The main purpose of this study was to investigate the effect of fleet management on organization performance from the perspective of employee the case of Bollore Logistics Ltd. The study sought to explore the impact of fleet management on the organization’s performance in Bollore Logistics Ltd. The study was guided by the objectives that included to find out the relationship between vehicle tracking and the organizational performance of Bollore Logistics Ltd, to establish the relationship between vehicle fuel management and organizational performance of Bollore Logistics Ltd and to find out the relationship between driver management and organizational performance of Bollore Logistics Ltd. The study population comprised 30 participants that were drawn from selected departments at Bollore Logistics Ltd. A total of 30 questionnaires were successfully returned to yield a 100% overall response rate. Findings deduced from the study proved that a positive correlation existed between fleet management and organization performance. Conclusions and recommendations that for Bollore Logistics Ltd to succeed requires to have constant change and upgrade on their fleet and adopt innovation in managing the fleet.
This is a dissertation.